1984
DOI: 10.1007/bf01015221
|View full text |Cite
|
Sign up to set email alerts
|

Circannual rhythm of exercise metabolic rate in humans

Abstract: Exercise metabolic rate was established by indirect calorimetry in 18 healthy subjects. Each subject was tested every month for 1 year. Four variables demonstrated a circannual rhythm and its acrophases occurred in the following months: RQ in October; exercise metabolic rate in April; acceleration of heart rate during exercise in February; percentage of body fat in August.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…We found no annual variation in self-reported physical activity or measured BMI but a strong seasonal variation in WHR. Variation in WHR represents variation in abdominal fat mass and is supported by a study showing body fat to be highest in the summer and early fall (29). Zahorska-Markiewicz and Markiewicz (29) suggest that fat is the main fuel oxidized in the winter, and a lower utilization of fat as a metabolic substrate in summer could account for accumulation of body fat.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We found no annual variation in self-reported physical activity or measured BMI but a strong seasonal variation in WHR. Variation in WHR represents variation in abdominal fat mass and is supported by a study showing body fat to be highest in the summer and early fall (29). Zahorska-Markiewicz and Markiewicz (29) suggest that fat is the main fuel oxidized in the winter, and a lower utilization of fat as a metabolic substrate in summer could account for accumulation of body fat.…”
Section: Discussionmentioning
confidence: 95%
“…Variation in WHR represents variation in abdominal fat mass and is supported by a study showing body fat to be highest in the summer and early fall (29). Zahorska-Markiewicz and Markiewicz (29) suggest that fat is the main fuel oxidized in the winter, and a lower utilization of fat as a metabolic substrate in summer could account for accumulation of body fat. Visceral fat is readily mobilized by lifestyle changes in energy balance (30), making seasonal variation in WHR a plausible explanation for the observed inverse relationship between testosterone levels and WHR during the year.…”
Section: Discussionmentioning
confidence: 95%
“…In their study of plasma glucose in humans, Suarez and Barrett-Connor (14) noticed that a history of recent weight gain corresponded to the season of maximum fasting plasma glucose, which was winter as was mentioned above. Measurements by Zahorska-Markiewicz and Markiewicz (35) in Poland indicated that physical fitness is higher in summer, that fat is the main fuel in winter, and that carbohydrate is the main fuel in summer, as judged by the respiratory quotient. The efficiency of weight loss by dietary restriction in obese women was season dependent, with the most marked weight loss in spring and the worst results in winter (36).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, exercise provides an excellent opportunity to study the dynamic balance between oxidant challenge and antioxidant defense in a biological system. Although abundant data on the influence of exercise on oxidant/antioxidant status in men and women exist, to the best of our knowledge the only reports of circannual rhythms of exercise are the one by Zahorska-Markiewicz and Markiewicz (1984), which deals with variables like heart and metabolic rate, and the recent data by Pivarnik et al (2003) about seasonal frequency, intensity and energy expenditure in exercise.…”
Section: Introductionmentioning
confidence: 95%